Evaluating ribosomal frameshifting in CCR5 mRNA decoding - Khan, Yousuf A.; Loughran, Gary; Steckelberg, Anna-Lena; Brown, Katherine; Kiniry, Stephen J.; Stewart, Hazel; Baranov, Pavel V.; Kieft, Jeffrey S.; Firth, Andrew E.; Atkins, John F. (Nature (London), 2022)
PCR with reverse transcription (RT-PCR) of reporter RNAs showed that for cells transfected with the CCRS reporters, there was substantially less full-length cDNA and a simultaneous appearance of smaller molecular mass products (Fig. 1g). [...]the claim that the frameshift site is highly conserved among higher primates does not indicate that the (putative) frameshift signal is subject to purifying selection. [...]a rabbit reticulocyte lysate in vitro translation system was programmed with capped RNAs (Fig. 2j). Methods Alignment of CCR5 slippery sites The NCBI RefSeq database was searched with tblastn using the human CCR5 amino acid sequence derived from mRNA accession NM_000579.3 as query on 4 December 2018 using default parameters, with the number of hits expanded from 100 to 500.